Improving Oral Intake of Essential Oil Blends Using A Novel Formulation of Biodegradable Chitosan/Lecithin Nanoparticles - Al-Ogaidi, Israa Ali Zaidan (Iraqi Journal of Science, 2021)
A novel, safe and efficient method was developed to encapsulate a blend of essential oils (EOs) into biodegradable nanoparticles (NPs). The biodegradable and biocompatible nanoparticles were made from chitosan (CH) and lecithin (LE) . The quality of the essential oils was verified using gas chromatography/mass spectrometry (GC/MS). The synthesis of nanoparticles included emulsification, followed by sonication, homogenization, and extrusion. Transmission electron microscopy (TEM) indicated that the nanoparticles were spherical in shape with sizes ranging from 25 to 70 nm, while dynamic light scattering (DLS) showed high negative zeta potentials. The stability of the final formula was evaluated in gastric and intestinal fluids. The chitosan/lecithin encapsulated EOs exhibited promising antimicrobial activity against the multi-drug resistant bacteria Salmonella typhi.